Mesoporous ZnZSM-5 zeolites synthesized by one-step desilication and reassembly: a durable catalyst for methanol aromatization. Issue 28 (29th February 2016) - Wang, Xiaoxing; Zhang, Junfeng; Zhang, Tao; Xiao, He; Song, Faen; Han, Yizhuo; Tan, Yisheng
Abstract : A mesoporous ZnZSM-5 zeolite synthesized by simple alkaline desilication and CTAB-mediated reassembly shows obviously improved catalytic stability for methanol aromatization. Abstract : Mesoporous ZnZSM-5 zeolites were synthesized by introducing zinc directly into an alkaline and surfactant solution. The characterizations reveal that the presence of CTAB is favorable for the recrystallization of zeolite structural units. The amount of strong acid sites of mesoporous zeolites decreased, while the amount of medium acid sites of mesoporous zeolites (especial zinc-containing) increased. The amount of Lewis acid sites increased while the amount of Brønsted acid sites obviously decreased. For mesoporous ZnZSM-5, the emergence of a new species (ZnOH + ) further increased the amount of Lewis acid sites. Both the external surface area and mesopore volume of mesoporous ZnZSM-5 gradually decreased with increasing zinc content. Most of zinc species introduced during desilication and reassembly dispersed on the surface of zeolites, but the addition of zinc species had no obvious influence on the zeolite morphology. The catalytic performance of the obtained materials was investigated via aromatization of methanol. The results show that BTX (benzene, toluene, and xylene) selectivity over mesoporous ZnZSM-5 gradually increases with increasing zinc content, and is much higher than that of mesoporous HZSM-5. However, the BTX selectivity of mesoporous HZSM-5 is obviously lower than that of HZSM-5 due to its much lower strong acid sites and larger pore size. The strong Brønsted acid sites, the Zn-Lewis acid sites and mesoporous channels have a synergistic effect on methanol aromatization over mesoporous ZnZSM-5 catalysts. Additionally, compared with HZSM-5, improvement in catalyst lifetime of MHZSM-5 and MZnZSM-5-2 is achieved by introducing additional mesoporous channels and decreasing the amount of strong acid sites.